PEMBUATAN KARBON AKTIF DARI PELEPAH KELAPA SAWIT MENGGUNAKAN AKTIVATOR H 2 O SEBAGAI ADSORBEN - Amalia Aisha Noer; Awitdrus '; Usman Malik (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Activated carbon has successfully been made from a raw material of oil palm midrib atcarbonization temperature of 500°C for 20, 40 and 60 minutes. Physical activation wasconducted using steam as activator agent at temperature of 900°C for 20, 40 and 60minutes. The objective of this research was to study the characteristics of oil palm midrib as an activated carbon. The characteristics of activated carbon were characterized by loss weight analysis, proximate and ultimate test, iodine number and yield. The results showed that the best activated carbon were the samples that were carbonized and activated in 60 minutes with loss weight of 67,8%, water content of 5,5%, ash content of 8%, carbon content of 50,23%, hydrogen of 3,38%, and oxygen of 43,18%. The iodine number analysis confirmed the iodine number of 200% which was higher than the Indonesian Industrial Standard values and yield of 42,3%.